The Potential of Paku Gajah (Angiopteris evecta) as Antitumor Through In Vitro and In Silico Studies - Rasyid, Herlina; Asmirah, Asmirah; Firdausiah, Syadza; Arief, Ihsanul; Soekamto, Nunuk Hariani (Universitas Jenderal Soedirman, 2024)
ABSTRACT. Paku gajah (Angiopteris evecta) is one of the largest ferns which has been used empirically by the Dayak tribe of Kalimantan, Indonesia as a traditional medicine to treat various diseases, one of which is tumors. This research aims to determine the potential utilization of A. evecta stem extract as an antitumor by secondary metabolites analysis, toxicity and antitumor assay. The methods used in this study were gradual maceration using three solvents (n-hexane, ethyl acetate, and methanol), phytochemical screening, toxicity test, antitumor activity assay with the Alamarblue method, Liquid Chromatography-Mass Spectrometry (LC-MS) analysis, and molecular docking analysis. This study indicated that A. evecta stem extract contained secondary metabolites such as flavonoids, saponins, tannins, and steroids. The ethyl acetate and methanol were found as toxic extracts with LC50 130.67 and 314.31 µg/mL, respectively. In line with the toxicity, the antitumor activity of the ethyl acetate extract was the highest with an IC50 of 240.94 µg/mL and phytochemical analysis revealed the presence of violanthin and angiopteroside in the extract. Molecular docking showed that the binding energy and inhibition constants of violanthin and angiopteroside against receptors were higher than standard ligand F82. The interaction between violanthin and the receptor results five hydrogen-bond (H-bond) with Lys920, Cys919, Asp1046, and Leu840, while the angiopteroside produces four H-bonds with Leu836, Leu834, and Arg831. Keywords: Antitumor, molecular docking, paku gajah (Angiopteris evecta).